From Archaeology of Thought. Inspired by Readings of Walks with Aristotle - Mamzer, Henryk (Sensus Historiae, 2024)
The text presents a juxtaposition of two opposing perspectives on the sources of human ideas, found in: (1) Z. Freud’s views on biological inheritance and Jungian archetypes; and (2) B. Kotowa’s ideas on the concept of cultural transmission. The biological foundation of archetypal forms, contained in the collective unconscious, according to Kotowa, is always considered from the standpoint of cultural order. The entire concept, referred to as “archaeology of thought,” refers on the one hand to Aristotle's concept of the Prime Mover, and on the other hand to Freudian archaeology as a psychoanalytic interpretation of culture, i.e., the archaeology of the subject or the archaeology of ourselves. Our perception of the past is shaped in the reality in which we are situated here and now, rather than in the one that is the subject of our investigation.